Insulin resistance in the ХХІ century: multimodal approach to assessing causes and effective correction - M.I. Bobryk; T.M. Tutchenko; I.V. Sidorova; O.A. Burka; O.I. Krotyk; A.V. Serbeniuk (Publishing House TRILIST, 2021)
In a broad sense, insulin resistance (IR) is the impairment of the biological response of target tissues to insulin stimulation. IR plays a leading role in the development of metabolic syndrome, the global prevalence of which continues to grow, despite the significant efforts of medical systems. The multicomponent nature of metabolic syndrome implies its complex and heterogeneous pathogenesis, knowledge about which is annually updated with new details as a result of scientific research. This review systematizes the results of recent studies on risk factors and pathogenetic links in the development of IR, prospects and existing experience of using these data in clinical practice with an emphasis on assessing the level of melatonin and vitamin D. The issue of timely and reliable laboratory confirmation of IR is relevant not only for endocrinologists, but also for specialists in almost all areas. In clinical use apart from indirect methods of IR-assessment like HOMA-IR, there is an informative test intact proinsulin. Recently, the increasing attention of researchers is attracted by such factors of the development of IR as vitamin D deficiency and disturbances in chrono- and biorhythms. Today, their role in the pathogenesis of IR can be considered proven, which makes it possible to consider vitamin D and melatonin as therapeutic agents in an integrated approach to the prevention and correction of IR. Statistical analysis of the research results of the "DILA" Medical Laboratory and clinical data provided by the Department of Endocrinology of the O.O. Bogomolets National Medical University also showed an association of vitamin D and melatonin levels with IR. Thus, a review of scientific sources over the last 5 years clearly demonstrates the growing urgency of the problem of IR and metabolic syndrome, the need to reconsider their management from assessing traditional etiopathogenetic factors (alimentary) to taking into account the maximum spectrum of genetic aspects and exogenous impacts. An important place among the latter belongs to an objective assessment of the vitamin D and melatonin levels for adequate pharmacological correction.